Facilitators and barriers to infant post-natal HIV prophylaxis, a qualitative sub-study of the PROMISE-EPI trial in Lusaka, Zambia - Mennecier, Anaïs; Matoka, Beauty; Wilfred-Tonga, Maria Melany; Chunda-Liyoka, Catherine; Mwiya, Mwiya; Nagot, Nicolas; Molès, Jean-Pierre; Van de Perre, Philippe; Kankasa, Chipepo; King, Rachel; , for the PROMISE-EPI social science sub-study group (Frontiers in Public Health, 2023)
Background Infant post-natal prophylaxis (PNP) is used to prevent HIV transmission through breastfeeding. The WHO edited recommendations but so far there is no consensus on the duration of prophylaxis and the type of drug used depends on national guidelines. In Zambia, the national recommendations include a three-drug prophylaxis, composed of a dispersible combined tablet of zidovudine (AZT) and lamivudine (3TC) and an oral suspension of nevirapine (NVP) for 12 weeks or until the mother’s viral load is <1000 cp/mL. The PROMISE-EPI study, modified the PNP regimen to lamivudine only, initiated at 6 weeks and continued until 12 months to all HIV exposed uninfected infants of virally unsuppressed mothers. Our aim in this analysis was to identify barriers and facilitators to this extended PNP, the keystone toward an effective prevention. Methods Individual interviews and focus group discussion (FGD) were conducted with PROMISE-EPI participants who had received prophylaxis for their children from the national program up to 6 weeks and then lamivudine oral solution in PROMISE-EPI study. Health care providers and PROMISE-EPI staff were also interviewed. Sessions were recorded, transcribed verbatim and translated from local languages into English. An initial code-book was designed and then adapted on the basis of the emerging themes, to allow a descriptive thematic analysis. Results More barriers to PNP adherence were identified with triple drug prophylaxis than with lamivudine. These barriers were related to the formulation and bitter taste of AZT/3TC tablets. The ready to use formulation and sweet taste of lamivudine syrup were appreciated by mothers. Extended PNP proposed in the PROMISE-EPI study was globally well accepted and strategies were found to increase adherence. Adherence to lamivudine appeared to be better than the mothers’ adherence to their own antiretroviral therapy. Conclusion Accompanying mothers living with HIV and giving them the choice of the PNP to prevent transmission via breastfeeding (type of PNP regimen and extended PNP in non-adherent mothers), may be one of the keys to reducing the burden of pediatric HIV acquisition in low and middle income countries.